The effect of vertical brand extensions on consumer-brand relationships in South Africa - O. Muroyiwa; R. Abratt; M. Mingione (South African Journal of Business Management, 2017)
The purpose of this research is to evaluate the impact of the introduction of vertical brand extensions on Consumer-Brand Relationships (CBRs) in the mobile phone market. In particular, we aim at exploring the effect vertical brand extensions that luxury and functional brands have on consumers' perceptions, as well as the effect the extensions will have on CBRs. This study pursues a quantitative approach, developing and testing four hypotheses on the influence vertical brand extensions have on four CBR-related constructs, namely brand attachment, brand trust, brand commitment and brand identification. The elicited context is the South African market and the selected brands are Apple, to represent luxury brands, and Samsung, representative of functional brands. Results only partially confirm previous research on vertical brand extension. Supporting previous studies, a vertical step-down extension has been found to have a stronger negative impact on brand commitment for the luxury brand than for the functional one. However, findings disconfirm the literature in revealing a stronger negative impact on the functional brand than the luxury brand and a positive effect on the brand attachment of both brands, especially the functional brand.
Keywords: 650